Love and math : the heart of hidden reality - Frenkel, Edward, 1968- (New York : Basic Books, a member of the Perseus Books Group, 2014)
"Tells the two intertwined stories of mathematics and the adventure of one man in learning it. The result is a story about how he became one of the twenty-first century's leading mathematicians, working on one of the biggest ideas to come out of mathematics in the last 50 years: the Langlands Program."--Provided by publisher.
Cover title: Love & math.
Includes bibliographical references (p. 247-282) and index.
Adult
Adult
Keywords: Frenkel, Edward, -- 1968-; Frenkel, Edward, -- 1968-; Mathematicians -- United States -- Biography; Mathematics -- Miscellanea; Mathematicians -- United States -- Biography; Mathematics -- Miscellanea